2010
DOI: 10.1097/hco.0b013e32833f0318
|View full text |Cite
|
Sign up to set email alerts
|

The future of regenerating the myocardium

Abstract: In today's cardiovascular field, once a cardiomyocyte is lost it is lost for good, without any form of direct therapeutic option. For these reasons, cell therapy justifies our continued attention and efforts, and may constitute the holy grail of cardiovascular therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
0
11
0
2
Order By: Relevance
“…However, despite the emerging concept that satellite and endothelial cells co-operatively interact during angio-myogenesis [37], [38] and that VEGF plays an essential role in this bidirectional interaction [39], the involvement of this growth factor on muscle repair/regeneration has been poorly characterized. Of interest, recent observations show that VEGF is up-regulated in hypertrophic and hypoxic myofibres [40], [41], providing the basis for considering VEGF as a multifaceted factor for muscle growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the emerging concept that satellite and endothelial cells co-operatively interact during angio-myogenesis [37], [38] and that VEGF plays an essential role in this bidirectional interaction [39], the involvement of this growth factor on muscle repair/regeneration has been poorly characterized. Of interest, recent observations show that VEGF is up-regulated in hypertrophic and hypoxic myofibres [40], [41], providing the basis for considering VEGF as a multifaceted factor for muscle growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…We used a young, otherwise healthy porcine model of chronic ischemia. Most regenerative therapies are positive in these “normal” models, and nearly all preclinical studies utilizing diseased models such as a high‐fat–fed models are negative, as are nearly all clinical trials 25, 26, 27, 28. Finally, we used male pigs in our current research to decrease variability; in the future we will use female pigs as well.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proposed strategies to restore the damaged myocardium have focused on external interventions such as cell, tissue, or full organ replacement [24]. In contrast to other non-cardiomyogenic stem cell types such as mesenchymal precursor cells that confer benefits through paracrine effects [25], transplanted hPSC-CMs also have the potential to achieve true contractile tissue regeneration [26]. Indeed, experiments in small and large animal models have demonstrated that hPSC-CMs transplanted to sites of ischemic injury survive and can electrically couple to the host myocardium [27–35].…”
Section: Applications Of Pluripotent Stem Cell-derived Cardiomyocytesmentioning
confidence: 99%